Ekstrasi Fitur Berbasis Tekstur Menggunakan Distribusi Statistik Pada Sistem Temu Balik Citra - Kapitan, Inten; Aliandu, Paulina; Nani, Paskalis Andi (MEANS (Media Informasi Analisa dan Sistem), 2019)
Feature extraction is a method to capturing visual content of images for indexing and retrieval. This research using texture, low level image feature as gernal (visual) feature for extracting feature of images. Image texture measurement using selected histogram based features such as mean (average of grey level), standard deviation, skewness, energy and smoothness. The basis of measure of similarity in this research is Canberra distance. Performance of CBIR system used precision and recall.